A meta-analysis comparing the prognostic accuracy of six diagnostic tests for predicting perioperative cardiac risk in patients undergoing major vascular surgery. Issue 11 (31st October 2003) - Kertai, M D; Boersma, E; Bax, J J; Heijenbrok-Kal, M H; Hunink, M G M; L'talien, G J; Roelandt, J R T C; van Urk, H; Poldermans, D
Abstract : Objective: To evaluate the discriminatory value and compare the predictive performance of six non-invasive tests used for perioperative cardiac risk stratification in patients undergoing major vascular surgery. Design: Meta-analysis of published reports. Methods: Eight studies on ambulatory electrocardiography, seven on exercise electrocardiography, eight on radionuclide ventriculography, 23 on myocardial perfusion scintigraphy, eight on dobutamine stress echocardiography, and four on dipyridamole stress echocardiography were selected, using a systematic review of published reports on preoperative non-invasive tests from the Medline database (January 1975 and April 2001). Random effects models were used to calculate weighted sensitivity and specificity from the published results. Summary receiver operating characteristic (SROC) curve analysis was used to evaluate and compare the prognostic accuracy of each test. The relative diagnostic odds ratio was used to study the differences in diagnostic performance of the tests. Results: In all, 8119 patients participated in the studies selected. Dobutamine stress echocardiography had the highest weighted sensitivity of 85% (95% confidence interval (CI) 74% to 97%) and a reasonable specificity of 70% (95% CI 62% to 79%) for predicting perioperative cardiac death and non-fatal myocardial infarction. On SROC analysis, there was a trend for dobutamine stress echocardiography to perform better than the other tests, but this only reached significance against myocardial perfusion scintigraphy (relative diagnostic odds ratio 5.5, 95% CI 2.0 to 14.9). Conclusions: On meta-analysis of six non-invasive tests, dobutamine stress echocardiography showed a positive trend towards better diagnostic performance than the other tests, but this was only significant in the comparison with myocardial perfusion scintigraphy. However, dobutamine stress echocardiography may be the favoured test in situations where there is valvar or left ventricular dysfunction.